Frequency of Y chromosome microdeletions and chromosomal abnormalities in infertile Thai men with oligozoospermia and azoospermia - Teraporn Vutyavanich (2018)
Aim: To investigate the possible causes of oligozoospermia and azoospermia in infertile Thai men, and to find the frequencies of Y chromosome microdeletions and cytogenetic abnormalities in this group. Methods: From June 2003 to November 2005, 50 azoospermic and 80 oligozoospermic men were enrolled in the study. A detailed history was taken for each man, followed by general and genital examinations. Y chromosome microdeletions were detected by multiplex polymerase chain reaction (PCR) using 11 gene-specific primers that covered all three regions of the azoospermic factor (AZFa, AZFb and AZFc). Fifty men with normal semen analysis were also studied. Karyotyping was done with the standard G- and Q-banding. Serum concentrations of follicle stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL) and testosterone were measured by electrochemiluminescence immunoassays (ECLIA). Results: Azoospermia and oligozoospermia could be explained by previous orchitis in 22.3%, former bilateral cryptorchidism in 19.2%, abnormal karyotypes in 4.6% and Y chromosome microdeletions in 3.8% of the subjects. The most frequent deletions were in the AZFc region (50%), followed by AZFb (33%) and AZFbc (17%). No significant difference was detected in hormonal profiles of infertile men, with or without microdeletions. Conclusion: The frequencies of Y chromosome microdeletions and cytogenetic abnormalities in oligozoospermic and azoospermic Thai men are comparable with similarly infertile men from other Asian and Western countries. © 2007 Asian Journal of Andrology. Shanghai Institute of Materia Medica, Chinese Academy of Sciences.